Combating Inequalities in Two-Way Language Immersion Programs: Toward Critical Consciousness in Bilingual Education Spaces - Cervantes-Soon, Claudia G.; Dorner, Lisa; Palmer, Deborah; Heiman, Dan; Schwerdtfeger, Rebecca; Choi, Jinmyung (Review of research in education, 2017)
This chapter reviews critical areas of research on issues of equity/equality in the highly prochimed and exponentially growing model of bilingual education: two-way immersion (TWI). There is increasing evidence that TWIprograms are not living up to their ideal to provide equal access to educational opportunity for transnational emergent bilingual students. Through a synthesis of research from related fields, we will offer guidelines for program design that attend to equality and a framework for future research to push the field of bilingual education toward creating more equitable and integrated multilingual learning spaces. Specifically, this review leads to a proposal for adding a fourth goal for TWI programs: to develop "critical consciousness" through using critical pedagogies and humanizing research.